2010
DOI: 10.1159/000272950
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Attenuates Anti-Metastatic Defense of the Lymph Nodes in Colorectal Cancer

Abstract: <i>Background:</i> Cancer-secreted high mobility group 1 (HMGB1) induces apoptosis of macrophages and suppresses the host anti-cancer immune system. <i>Objective:</i> We here examined the effect of HMGB1 on macrophages in the lymph nodes of colorectal cancer (CRC) patients. <i>Methods:</i> Regional lymph nodes of 50 Dukes C CRCs were compared with 50 Dukes B CRCs.<i> Results:</i> Dukes C tumors exhibited higher HMGB1 labeling indices and higher HMGB1 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
2
19
0
1
Order By: Relevance
“…HMGB1 binds to the endogenous receptor for advanced glycation endproducts [7], exogenous toll-like receptor 2/4/9 (TLR2/4/9) [8,9], and CD24/Siglec-10 [10], and induces the expression of proinammatory cytokines, chemokines, and adhesion molecules [3,6]. Although, HMGB1 was initially thought to be a late mediator of sepsis, recent data also indicated that HMGB1 is associated with many other pathological conditions, such as autoimmune disease [11], cancer [12][13][14], trauma, ischemia-reperfusion injury [15,16], tissue repair and regeneration [17,18], and cardiovascular diseases [19]. Furthermore, HMGB1 has restorative effects on CD4 1 T-helper cell modulation [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 binds to the endogenous receptor for advanced glycation endproducts [7], exogenous toll-like receptor 2/4/9 (TLR2/4/9) [8,9], and CD24/Siglec-10 [10], and induces the expression of proinammatory cytokines, chemokines, and adhesion molecules [3,6]. Although, HMGB1 was initially thought to be a late mediator of sepsis, recent data also indicated that HMGB1 is associated with many other pathological conditions, such as autoimmune disease [11], cancer [12][13][14], trauma, ischemia-reperfusion injury [15,16], tissue repair and regeneration [17,18], and cardiovascular diseases [19]. Furthermore, HMGB1 has restorative effects on CD4 1 T-helper cell modulation [20].…”
Section: Introductionmentioning
confidence: 99%
“…thought to be a late mediator of sepsis, recent data also indicated that HMGB1 is associated with many other pathological conditions, such as autoimmune disease [11], cancer [12][13][14], trauma, ischemia-reperfusion injury [15,16], tissue repair and regeneration [17,18], and cardiovascular diseases [19]. Furthermore, HMGB1 has restorative effects on CD4 1 T-helper cell modulation [20].…”
mentioning
confidence: 99%
“…In recent years, an increasing number of oncogenes related to the incidence, invasion, and metastasis of cervical cancer have been discovered, such as P53, bcl-2, survin, HPV E6 and E7 [6,7] . HMGB1 was discovered as a multifunctional cytokine involved in the growth, invasion, metastasis, clinical stage and prognosis of pancreatic cancer [8] , liver cancer, gastric cancer, melanoma, colon cancer [9] , breast cancer, bile duct cancer, and prostate cancer. Our early experiments demonstrated that HMGB1 protein in cervical squamous cell carcinoma (CSCC) especially in metastatic tissues was a strongly positive expression.…”
Section: Discussionmentioning
confidence: 99%
“…E-Selektin, selbst ein wichtiger Faktor bei der Metastasierung, scheint die zellul ä re Expression von HMGB1 im kolorektalen Karzinom zu drosseln, f ü hrt andererseits aber zu vermehrter HMGB1-Freisetzung in das extrazellul ä re Milieu, wo HMGB1 die vermehrte Expression von E-Selektin im Sinne eines positiven Feedback-Mechanismus f ö rdert [111] . Dar ü ber hinaus f ü hrt die Freisetzung von HMGB1 aus kolorektalen Tumorzellen zur Abnahme der Makrophagenzahlen in benachbarten, befallenen wie unbefallenen, Lymphknoten, was die Metastasierung in diesen Bereichen weiter beg ü nstigt [112,113] . Auch RAGE wurde im Fall von Pankreaskarzinomen mit der F ä higkeit zur Metastasierung assoziiert, wobei von drei Zelllinien mit verschieden hoher Metastasierungsneigung diejenige mit der niedrigsten RAGE-Expression die niedrigste Metastasierungsrate aufwies [114] .…”
Section: Gewebsinfiltration Und Metastasierungunclassified